Beneficial effects of N-acetylcysteine on hepatic oxidative stress in streptozotocin-induced diabetic rats - Rosa, Lucas Rodolfo de Oliveira [UNESP] (2018)
Diabetes is one of the leading diseases worldwide and, thus, finding new therapeutic alternatives is essential. The development of non-alcoholic fatty liver disease is a notable diabetic complication. Therefore, antioxidant therapy became a leading topic in the world of diabetes research. The objective of this present study was to evaluate the effects of antioxidant N-acetylcysteine (NAC) administration on serum biochemical parameters and oxidative stress parameters in hepatic tissue of the diabetic rats. Thirty-two animals were divided in 4 groups (n = 8): G1, normal rats; G2, normal rats + NAC; G3, diabetic rats; and G4, diabetic rats + NAC. Diabetes was induced in diabetic groups through streptozotocin. NAC administration was effective in improving hyperglycemia and hypoinsulinemia, as well as reducing serum alanine-aminotransferase and urea, hepatic triglycerides accumulation, and oxidative stress biomarkers in the diabetic liver, as well as improving the activity of hepatic antioxidant enzymes. This effect was likely due to NAC’s ability of restoring intracellular glutathione, an important compound for the antioxidant defense, as well as due to NAC’s direct antioxidant properties. Thus, NAC administration was useful for reducing hepatic oxidative stress and decreased the deposit of triacylglycerols, minimizing diabetic hepatic damage, making it a promising therapeutic adjuvant in the future.